Begonia thanhquyetii (B. sect. Petermannia, Begoniaceae), a new species from Quang Tri province, Central Vietnam - Duong, Nam Van; Nguyen, Cuong Huu; Le, Anh Tuan; Bui, Doi The; Dinh, Dien; Dang, Ha Van; Nguyen, Yen Thi; Tran, Hung The; Nguyen, Tuan Hoang; Averyanov, Leonid V.; Lin, Che Wei (Phytotaxa, 2026)
Begonia thanhquyetii, a new species from central Vietnam, is herein described and illustrated. It is morphologically most similar to B. baik in its creeping habit, rugose ovate leaves, and protogynous inflorescences. However, it differs in several key morphological characters, including stipules hirsute on the abaxial surface (vs. glabrous), bracts lacking glandular hairs along the margins (vs. glandular-ciliate), a pair of bracteoles present near the apex of the pistillate pedicel (vs. bracteoles absent), abaxial tepals of both staminate and pistillate flowers hirsute (vs. glabrous), and densely hirsute ovary (vs. glabrous). Following the IUCN Red List Categories and Criteria (Version 16), B. thanhquyetii is provisionally assessed as Least Concern (LC), pending further field surveys to clarify its distribution and population status.